2003
DOI: 10.1063/1.1597424
|View full text |Cite
|
Sign up to set email alerts
|

Gettering of Pd to implantation-induced nanocavities in Si

Abstract: Articles you may be interested inEffects of surface oxide layer on nanocavity formation and silver gettering in hydrogen ion implanted silicon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…88,132 Interestingly, it has been experimentally confirmed that metallic impurity atoms sre efficiently trapped near nanocavities in a silicon host matrix. 117,[133][134][135][136][137][138] Moreover, artificial cells with nanocavities can sequester poisonous heavy elements such as heavy metal atoms in the human body. 96 The void volume and inner skin associated with such nanocavities are the preferred trapping centers for impurities.…”
Section: Observationsmentioning
confidence: 99%
“…88,132 Interestingly, it has been experimentally confirmed that metallic impurity atoms sre efficiently trapped near nanocavities in a silicon host matrix. 117,[133][134][135][136][137][138] Moreover, artificial cells with nanocavities can sequester poisonous heavy elements such as heavy metal atoms in the human body. 96 The void volume and inner skin associated with such nanocavities are the preferred trapping centers for impurities.…”
Section: Observationsmentioning
confidence: 99%
“…7,8 For technical applications, clean nanocavities in Si are used as gettering centers for several heavy metals. 9 Increasing the H and He ion dose implantation, blistering, and exfoliation can occur: these phenomena have found practical applications in the wafer splitting technology. [10][11][12] The phenomena that cause the bubbles and cavities formation are several and they involve the implanted species as well as vacancies, interstitials, impurities, and dopants.…”
Section: Introductionmentioning
confidence: 99%
“…They are also produced as a consequence of nanocavity formation; however, the contribution of these dislocations to the gettering observed in nanocavity structures has not been investigated previously. Recently, 6 we observed that Pd-containing precipitates were concentrated along dislocations rather than being randomly distributed amongst nanocavities. To determine whether this effect was unique to Pd or common to other metals, Au and Cu were chosen for comparison.…”
mentioning
confidence: 96%
“…1 Consequently, the gettering of these unintentionally introduced impurities has been the topic of extensive research. Nanocavity structures, produced in Si by the implantation of H or He and subsequent annealing, are capable of gettering a wide range of metals, including Fe, 2 Co, 3 Ni, 4 Cu, 5 Pd, 6 Ag, 7 Pt, 8 and Au. 9 Precipitates of these metals and/or their silicides have been frequently observed in nanocavity structures, and it has been assumed that these precipitates were the result of excess metal filling in the nanocavities.…”
mentioning
confidence: 99%
See 1 more Smart Citation